Study on dynamic response of gravity dam under air blast load based on similarity law. (August 2022) - Zhang, Kefan; Lu, Fangyun; Peng, Yong; Li, Xiangyu
Graphical abstract: Highlights: The explosion test of the gravity dam model under the condition of air explosion was carried out. The changing trend of dynamic parameters under the explosion load of gravity dam are analyzed from the perspective of experiment and simulation. The similar laws of gravity dam models with different scales were summarized. Abstract: In order to study the dynamic response similarity law of concrete gravity dam under explosive load, the theoretical similarity model of gravity dam under explosive load was established, and the air explosion similarity law experiments with scaling coefficients of 0.01, 0.0075, 0.005 and 0.0025 were carried out. The shock wave characteristic parameters of air explosion and the similarity of structural dynamic response were analyzed. The simulation calculation was used to verify and extrapolate the experimental results. The comparison results showed that there is a similarity law between the explosion dynamic response parameters of each scaling model obtained by simulation calculation and experimental fitting data, which meets the theoretical results of similarity law. The method of expanding the dynamic parameters of small scale scaling model to large scale model is reasonable and reliable.